2022
DOI: 10.4103/jomfp.jomfp_44_21
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of density of microvessels and myofibroblasts with the aggressiveness of central giant cell granulomas of jaws

Abstract: Objectives: Central giant cell granuloma (CGCG) is a fairly common lesion involving the jaw bones. CGCG can show relatively innocuous biological behaviour or it may show clinicoradiological features suggestive of aggressive biological behaviour. To date, there are no histological parameters which can be used to predict the behaviour of these lesions. This study was conducted to assess the utility of parameters of angiogenesis, i.e., total vascular area (TVA), mean vascular area (MVA) and microvesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…About 80% of patients with periodontitis have subnormal tissue levels of CoQ10 in gingival biopsies. 94 A study found that CoQ10 could improve the gingival index as an auxiliary treatment to scaling and root planning. 95 Animal studies have also shown that dietary therapy with CoQ is able to reduce the progression of alveolar bone destruction.…”
Section: Pre Venti On or Tre Atment Of Peri Odontitis By Targ E Ting ...mentioning
confidence: 99%
“…About 80% of patients with periodontitis have subnormal tissue levels of CoQ10 in gingival biopsies. 94 A study found that CoQ10 could improve the gingival index as an auxiliary treatment to scaling and root planning. 95 Animal studies have also shown that dietary therapy with CoQ is able to reduce the progression of alveolar bone destruction.…”
Section: Pre Venti On or Tre Atment Of Peri Odontitis By Targ E Ting ...mentioning
confidence: 99%